Psycholinguistic Approach to Diagnostics and Modification of Individual Negative Core Beliefs - Zasiekina, Larysa (East European Journal of Psycholinguistics, 2015)
Psycholinguistic approach to diagnostics and modification of individual negative core beliefs. The present research provides the first evidence for psycholinguistics resources in diagnostics and modification of individual negative core beliefs. The individual core beliefs are treated as a system of subjectively experienced feeling of conscious or unconscious nature which expresses the attitude of personality towards himself/ herself, the world and other people. The results of the study were conceptually replicated: Participants’ core beliefs of lack of love were significantly correlated with their core beliefs of rejection (r=0.929, p<0.01); core beliefs of helplessness were significantly correlated with their core beliefs of low achievements (r=0.843, p<0.01); core beliefs of lack of control were significantly correlated with their core beliefs of helplessness (r=0.457, p<0.01). The results of correlation and descriptive analysis allowed revealing three groups of core beliefs and their distribution: rejection/ lack of love (17.3%); helplessness/low achievements (56.4%); helplessness/low control (25.6%). The most typical structure for propositions of different core beliefs was defined and the ways of their modification were suggested. References Anderson, J. R., Bower, G. (1974). Propositional theory of recognition memory. Memory & Cognition, 2, (3), 406–412. Bartlett, F. (1937). Cambridge, England: 1887–1937. American Journal of Psychology, 50, 97–110. Beck, A. T. (1976). Cognitive Therapies and Emotional Disorders. New York: New American Library. Beck, J. (2006). Kognitivnaya Terapya [Cognitive Therapy]. Moscow: Williams. Gould, J. A. (1978). Classic Philosophical Questions. Columbus: Bell and Howell Company. Haritonov, S. (2009). Rukovodstvo po kognitivno-povedencheskoy terapii [Manual for cognitibe and behavioral therapy]. Moscow: Psychotherapy. Rubinstein, S. (1989). Osnovy Obshchey Psychologii [Fundamentals of General Psychology]. Vol. 2. Moscow: Pedagogy. Vygotsky, L. (2001). Myshlenie i Rech [Thinking and Speech]. Moscow: Labirint. Westbrook, D., Kennerley, H., Kirk, J. (2014). Vstup u Kognitivnu Terapiyu [An Introduction to Cognitive and Behavioral Therapy]. Lviv: Svichado.